Sport without referees? The power of the International Olympic Committee and the social politics of accountability. (June 2016) - Nelson, Travis; Cottrell, M. Patrick
As governor of the world's pre-eminent sporting event, the International Olympic Committee exercises considerable power on the world stage. It has also been widely accused of corruption, corporate greed, and hypocrisy. However, for all of the media attention that the International Olympic Committee receives, it has seldom been examined theoretically and in the context of global governance. Why have so few stakeholders, including the states that host the events and field the teams, engaged in serious efforts to hold it accountable for its actions? In addition, what can the experience of the International Olympic Committee tell us about accountability in global governance more generally? Drawing from conceptual treatments of accountability, we argue that the challenges of the International Olympic Committee are rooted in the organization's social position and social power. The IOCs position in international society dilutes the base of potential accountability holders and exacerbates collective action problems, while its social power allows it to maintain a reputational shield to guard against meaningful accountability efforts. The article concludes by considering whether these dynamics ripple beyond the experience of the International Olympic Committee into other areas of global governance.